Lay attitudes toward trust, uncertainty, and the return of pediatric research results in biobanking. Issue 3 (2nd July 2016) - Lynch, John; Hines, Janelle; Theodore, Sarah; Mitchell, Monica
ABSTRACT: Background: Trust plays a role in participants' reactions to clinical residual biobanks. The purpose of this study is to assess whether trust in medical researchers and negative reactions to uncertainty influence the attitudes of parents of pediatric research participants toward the return of genomic research results from biobanking.Methods : Focus groups were conducted in collaboration with two community-based organizations. Participants completed a demographic questionnaire and the trust in research and intolerance of uncertainty scales. The focus groups were then conducted according to a thematic focus-group guide; discussions were transcribed and analyzed by two trained coders.Results : Emerging themes included the importance of returning research results to both children and parents, sharing results with few limitations based on a child's age, and the desire for results even when researchers had concerns about analytic validity. Negative reactions to uncertainty appear to have influenced only one theme: the paradoxical claim by participants with stronger reactions to uncertainty that they had a "right to information."Conclusion : Participants prefer to receive most or all of the results produced by genomic research, and they want their children, within variable age restrictions, to have access to that information as well.